Determining what represents value in the treatment of prurigo nodularis and its key unmet needs in Spain through Multi‐Criteria Decision Analysis - Juan Francisco Silvestre; M. J. Tribó; José C. Armario‐Hita; Miguel Ángel Calleja‐Hernández; Francisco Javier Ortiz‐Frutos; José Luis Poveda; John Shepherd; Esther Serra‐Baldrich (Wiley, 2024)
Abstract Background Prurigo nodularis (PN) is a chronic, debilitating dermatologic disease characterised by the presence of highly pruritic nodular lesions. PN highly impacts on patients' quality of life as there are no specific treatments available in Spain. Objectives Determine the main value drivers in the treatment of PN in Spain and its main unmet needs using Multi‐Criteria Decision Analysis (MCDA). Methods Literature review to synthesise relevant evidence in an evidence matrix based on the MCDA EVIDEM framework adapted to Spain. A multidisciplinary panel composed of dermatologists, hospital pharmacists and a patient weighted (5‐point scale; 0 minimum importance, 5 maximum importance) and scored each criterion included in the framework (from −5 to 5 or 0 to 5 depending on the criterion). Results were discussed in a reflective group session. Results PN was considered a severe (3.3 ± 0.7) and infrequent (2.0 ± 0.7) disease, with high unmet needs (4.2 ± 0.7) mainly due to the lack of available treatments with specific indication for PN. Current off‐label treatments were perceived to have limited efficacy/effectiveness (1.8 ± 1.1), an unfavourable long‐term safety profile (2.1 ± 0.9) and low therapeutic impact (1.7 ± 1.1). The measure of patient‐reported outcomes (2.7 ± 0.9) was perceived as important, but available tools are not specific. Although the cost of available treatments was not considered high (2.4 ± 1.5), experts agreed that PN is associated with moderately high other medical costs (3.6 ± 1.1) and indirect costs (3.1 ± 0.9). Experts considered that current guidelines and consensus (2.6 ± 0.7) are not clear on severity criteria and treatment algorithm. The quality of evidence (1.4 ± 0.5) of currently used off‐label treatments was perceived as low due to a lack of published clinical trials. Conclusions PN was considered a severe disease associated with relevant unmet needs, including the lack of specific and effective treatments for PN, the lack of consensus on the disease definition, defined severity criteria, prevalence estimations and awareness of PN in Spain.